Keputusan Anak Sekolah dan Bekerja: Pengaruh Aset Produktif Rumah Tangga di Indonesia - Ratih Ramadhani (Jurnal Ekonomi Pembangunan, 2019)
This study aims to look at the effect of productive assets and nonproductive household assets on school children's decisions and work in Indonesia by using ordered probit estimation techniques. The data used in this study are IFLS 2007. There are four school decisions, and work children sorted from the worst conditions to the best, namely children not in school and not working, children working, school and working children, and school children. The Principal Component Analysis (PCA) method calculates the Nonproductive asset index. This study found that productive assets and nonproductive assets of the household allow children to go to school and reduce the likelihood of children to work.